“The Other” Nabokov vs Nabokov-Sirin: Concerning One Occasional Mention in the Alexey Remisov’s Novel Music Teacher - Elena R. Obatnina (Studia Litterarum)
The article is devoted to the problem of reconstruction of the author’s strategy in the novel Music Teacher, which was connected with projections of the names mentioned in the title onto specific events of the literary life of Russian emigration of the early 1930s and personal creative biography. The central object of the study is the case of the single and unmotivated mention of “musician Nabokov” in the story “Industrial Horseshoe” (1931). The history of Remizov’s relationship with the composer N.D. Nabokov had so far remained unstudied. The reconstructed by archival materials event series of these relationships appears as a presupposition of the story “Industrial Horseshoe.” This information explains not only the motives of the reference to Nicolai Nabokov but also the role of this reference in the idea and plot of the story. Given the aesthetic and ethical differences between Remizov and the composer’s cousin, writer V.V. Nabokov (V. Sirin), the author of the article reveals the essence of the so-called “mutual dislike” of the two writers in the context of a specific period (1928–1931). The author also infuses a new view of the history “hostility” of the representatives of the older and younger generation of Russian foreign literature and describes this literary confrontation as a problem of linguistic self-identification of their younger peers and their choice of literary “teachers.”